2021
DOI: 10.1002/ece3.7438
|View full text |Cite
|
Sign up to set email alerts
|

Past connections with the mainland structure patterns of insular species richness in a continental‐shelf archipelago (Aegean Sea, Greece)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 71 publications
4
22
1
Order By: Relevance
“…Long-term area change through time due to island ontogeny is not the only factor to influence island diversity and to vary throughout the island's lifespan. At shorter-time scales, sea-level fluctuations also affect island area, as well as potentially altering island connectivity within an archipelago or with the mainland, by varying the distance between landmasses, for example through the formation of temporary land-bridges (Ali and Aitchison, 2014;Fernández-Palacios et al, 2016;Hammoud et al, 2021). Dynamic island connectivity has left signatures on contemporary total and endemic island species diversity (Weigelt et al, 2016;Norder et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term area change through time due to island ontogeny is not the only factor to influence island diversity and to vary throughout the island's lifespan. At shorter-time scales, sea-level fluctuations also affect island area, as well as potentially altering island connectivity within an archipelago or with the mainland, by varying the distance between landmasses, for example through the formation of temporary land-bridges (Ali and Aitchison, 2014;Fernández-Palacios et al, 2016;Hammoud et al, 2021). Dynamic island connectivity has left signatures on contemporary total and endemic island species diversity (Weigelt et al, 2016;Norder et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, phylogeographic and paleo-island biogeography studies have revealed that land-bridge islands have unique colonisation, migration and speciation dynamics that often do not fit classic oceanic-island-centric island biogeography (e.g. Papadopoulou and Knowles (2015); Hammoud et al (2021)). The land-bridge implementation with different rates of land-bridge colonisation used in this study is consistent with how different taxonomic groups may utilise land-bridges to colonise at different rates.…”
mentioning
confidence: 99%
“…Hammoud et al (2021) examined the relationship between island area and species richness in the Aegean Islands across multiple angiosperm taxa, taking into account historical sea-level change over the Quaternary. They find that true islands, which were historically unconnected to the mainland, exhibit stronger correlations between island area and endemic species richness relative to land-bridge islands.…”
Section: Pleistodist Applications and Case Studiesmentioning
confidence: 99%
“…Yet, empirical species distributions across island archipelagos highlight numerous exceptions. At macroecological scales, the distributions of terrestrial megafauna across the Sundaic and Wallacean regions (Wallace 1869; Lohman et al 2011) and the decoupling of species-area correlations on land-bridge islands in the Aegean Sea (Hammoud et al 2021) illustrate how land bridges can facilitate dispersal, colonisation, and biotic homogenisation between distant islands. Phylogeographic studies have also demonstrated that patterns of intraspecific genetic differentiation within island archipelagos are correlated with land-bridge connectivity (Leonard et al 2015; Cros et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The fauna (and flora) of the Aegean has emerged and diversified due to a complex mix of vicarianistic and dispersal events, as well as the longlasting human presence, which has continuously interacted and impacted with the Aegean environment for more than 10,000 years (Poulakakis et al 2014). Recently, Hammoud et al (2021) highlighted that in terms of processes affecting species richness patterns, continental archipelagos differ fundamentally from oceanic systems because episodic connections with the mainland have profound effects on the biota of land-bridge islands.…”
Section: Introductionmentioning
confidence: 99%